Greening the marine map: a comprehensive study of China’s marine ecological and economic synergy - Li, Zechen; Lin, Hanqian; Zhang, Xuemei (Frontiers in Marine Science, 2024)
This paper examines the coupling coordinated development dynamics between marine ecological governance and marine economic development in China's coastal provinces. The data on marine ecological governance and economic development of China's 11 coastal provinces were comprehensively analysed from 2011 to 2021 by constructing a multi-dimensional evaluation index system and applying the global entropy weight method, the coupled coordination degree model, the Theil index decomposition method, and the geodetector detector. According to the results, the Northern marine economic circle outperforms the Eastern and Southern ones regarding marine ecological governance, while the Eastern marine economic circle is the most advanced in marine economic development. The coupling coordination degree model (CCD) analysis indicates that Guangdong, Shandong, Hebei, and Jiangsu have the best coupling coordinated development, while Hainan, Tianjin, and Guangxi are at the bottom. The Theil index decomposition method indicates that intra-regional disparities are the primary cause of coupling coordinated regional development variations. At the same time, the results of the geographic detector further substantiate that energy structure, degree of industrial agglomeration, and foreign overseas direct investment are the principal influencing factors. The study presents policy recommendations derived from the findings intended to foster the integrated advancement of marine ecology and economy in coastal provinces, reduce regional development disparities, and establish a scientific foundation for achieving a sustainable marine economy.